Accounting students' perceptions on e-learning during the Covid- 19 pandemic: preliminary evidence from Saudi Arabia - El‐Sayed Ebaid, Ibrahim (Journal of Management and Business Education, 2020)
This study aims to discover accounting students’ opinions of e-learning, which was applied as an alternative to the traditional education system in Saudi universities during the Covid- 19 pandemic. This study is a cross-sectional survey that sought to collect field data on accounting students’ perceptions of e- learning in Saudi Arabia. The findings of the study revealed that the majority of the accounting students expressed that they did not benefit from e-learning, either in increasing flexibility in their study of accounting courses, facilitating their study of accounting courses, improving their communication with teachers, improving their communication with other students or improving their possibilities to solve problems connected to the study of accounting courses. The majority of students have agreed that the most important disadvantages of e-learning are: lack of human contact, the technical problems and too much dependence on computers. In general, this study contributes to the body of research on the benefits of e- learning in higher education. In particular, this study is the first study to evaluate the decision of the Ministry of Higher Education in Saudi Arabia to implement e-learning as a complete alternative to the traditional education system.